High-selectivity separation membrane and preparation method thereof

By designing the structures of dynamic hydrophobic layer, basement film, nanosieve layer, deposited film and selective capture layer in the separation membrane, the problem of low selectivity of nitrate and nitrite in conventional membrane separation technology is solved, and efficient separation and long-term stability are achieved.

CN119819132AActive Publication Date: 2025-04-15SHENZHEN ENERGY RESOURCES COMPREHENSIVE DEV CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510310107.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-15
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

In the prior art, conventional membrane separation technology has low selectivity for nitrates and nitrites in desulfurization wastewater, making it difficult to achieve efficient removal.

Method used

A highly selective separation membrane is used, and its structure includes a dynamic hydrophobic layer, a base film, a nanosieve layer, a deposited film and a selective capture layer. The formation of a selective capture layer is facilitated by specific preparation methods including microfluidic aerosol spraying method, calcination to form a nanosieve layer, asymmetric pulsed electric field treatment to form a deposited film, and carbon dioxide gas to facilitate the formation of a selective capture layer.

Benefits of technology

It significantly improves the separation efficiency of nitrate and nitrite, reduces interference from other inorganic salts, and ensures the long-term stability and efficient performance of the separation membrane in harsh chemical environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819132A_ABST
    Figure CN119819132A_ABST
Patent Text Reader

Abstract

The invention discloses a high-selectivity separation membrane and a preparation method thereof, the high-selectivity separation membrane comprises a dynamic hydrophobic layer as well as a basement membrane, a nano sieve layer and a deposition and selective capture layer which are connected in sequence, and the dynamic hydrophobic layer is arranged on the outer sides of the basement membrane, the nano sieve layer and the deposition and selective capture layer. Through the basement membrane, the nano sieve layer, the deposition membrane and the selective capture layer, when the separation membrane is used for treating desulfurization wastewater, nitrate and nitrite can be separated with high selectivity, so that interference of other inorganic salts is reduced, the separation efficiency of the separation membrane is remarkably improved, large molecules and particles can be effectively separated through the porous structure of the basement membrane, and the separation efficiency is improved. Under the action of a deposited film, the nano sieve layer can further improve the blocking effect on other macromolecules or particles, the capture layer is selected to selectively adsorb # imgabs0 and # imgabs1 through electrostatic interaction, the # imgabs0 and # imgabs1 are temporarily retained in the capture layer, and then # imgabs2 and # imgabs3 are discharged from the interior of the capture layer in cooperation with flowing of desulfurization wastewater to achieve separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of separation membrane preparation, and in particular to a high-selectivity separation membrane and a preparation method thereof. Background Art

[0002] With the acceleration of industrialization, wastewater discharge has increased year by year. Among them, desulfurization wastewater has attracted much attention due to its high pollution. In desulfurization wastewater, the concentrations of nitrate and nitrite are usually high. These substances are not only the main cause of eutrophication of water bodies, but may also pose a serious threat to aquatic ecosystems and human health.

[0003] In the prior art, conventional membrane separation technology is used in the treatment of desulfurization wastewater. Conventional membrane separation technology has low selectivity for ions during the separation process, resulting in the simultaneous permeation of small molecular ions such as nitrate and nitrite and other inorganic salts, forming a mixture with no obvious concentration difference, which makes it difficult to achieve efficient removal. In addition, during the separation process, small molecular ions such as nitrate and nitrite will compete with other inorganic salts to pass through the membrane pores, which further affects the separation effect.

[0004] Therefore, a high-selectivity separation membrane and a preparation method thereof are proposed to solve the above-mentioned problem of low selectivity for specific ions. Summary of the invention

[0005] The object of the present invention is to provide a high-selectivity separation membrane and a preparation method thereof, which solves the problem of low selectivity for specific ions.

[0006] To achieve this object, the present invention adopts the following technical solutions: A highly selective separation membrane comprises a dynamic hydrophobic layer and a base membrane, a nano-sieve layer, a deposition and selective capture layer connected in sequence, wherein the dynamic hydrophobic layer is arranged on the outside of the base membrane, the nano-sieve layer, the deposition and selective capture layer.

[0007] A method for preparing a highly selective separation membrane, used for preparing the highly selective separation membrane described above, the method comprising the following steps: Step S1, mixing sulfonated polyaryletherketone with sulfolane / tetrahydrofuran to obtain a mixed solution, and forming the mixed solution by microfluidic aerosol jetting, and drying and solidifying the mixed solution to obtain a basement membrane; Step S2, providing a phosphate buffer solution, immersing the surface of the basement membrane in the phosphate buffer solution, adding tetraethyl orthosilicate and ammonia water to the phosphate buffer solution, and after the reaction is completed, calcining the basement membrane to form a nano-sieve layer on the surface of the basement membrane; Step S3, providing an acidic ISE-PEL polyelectrolyte solution, immersing the nano-sieve layer on the surface of the substrate membrane therein, and subjecting the solution to an asymmetric pulse electric field treatment to form a deposited film on the nano-sieve layer; Step S4, providing a mixed solution of ammonium cerium nitrate and 2-methylimidazole, immersing the deposited film on the nano-sieve layer on the surface of the substrate film in the mixed solution, and introducing carbon dioxide gas to form a selective capture layer on the deposited film; Step S5, providing an amphiphilic triphenylene derivative solution, and spin coating it on the entire base film, and after it is cured by ultraviolet light, a dynamic hydrophobic layer is formed on the entire base film.

[0008] The step S1 specifically includes: Step S11, after mixing the sulfonated polyaryletherketone and sulfolane / tetrahydrofuran, stirring at a constant temperature of 35-45° C. for 6-8 hours, and after the solution is stirred until it is completely transparent, a mixed solution is obtained; Step S12, injecting the mixed solution into a microfluidic aerosol spraying device, and under the impetus of high-purity nitrogen, spraying the mixed solution onto a low-temperature cold plate through a nozzle on the microfluidic aerosol spraying device to solidify and form, thereby obtaining a basement membrane prototype; Step S13, placing the basement membrane prototype in a drying device, and introducing carbon dioxide, and obtaining the basement membrane after drying is completed.

[0009] In the step S11, the mass percentage of the sulfonated polyaryletherketone in the mixed solution is 10-20%, and the viscosity of the mixed solution is 50-200 mPa·s; In step S12, the nozzle diameter is 10-50um, the injection pressure is 100-300kPa, the nozzle movement speed is 5-20mm / s, the nozzle injection flow rate is 1-10m / s, the distance between the nozzle and the cold plate is 1-3mm, the cold plate temperature is -30°C, and the molding time is 5-10min; In the step S13, the drying temperature in the drying equipment is 35-45°C, the drying pressure is 10-12MPa, and the drying time is 1-2h.

[0010] The step S2 specifically includes: Step S21, mixing disodium hydrogen phosphate dihydrate and potassium dihydrogen phosphate to obtain a phosphate buffer, and then placing the surface of the basement membrane obtained in step S1 in the phosphate buffer and letting it stand for 10-30 minutes; Step S22, adding tetraethyl orthosilicate into the phosphate buffer solution and stirring once, then adding ammonia water dropwise and stirring twice, and allowing the surface of the basement membrane to stand for 1-3 hours; Step S23, after the basement membrane is taken out, cleaned and dried, the basement membrane is calcined through a three-stage calcination.

[0011] In the step S21, the molar ratio of the disodium hydrogen phosphate dihydrate to potassium dihydrogen phosphate is 1:1, the pH value of the phosphate buffer is 7.0, and the basement membrane surface is left to stand for 20 minutes; In the step S22, the mass percentage of the tetraethyl orthosilicate in the phosphate buffer is 1-5%, the mass percentage of the ammonia water in the phosphate buffer is 0.5-2%, and the balance is the phosphate buffer. The concentration of the tetraethyl orthosilicate is 0.05-0.1M, the concentration of the ammonia water is 25-28%, the first stirring time is 8-12min, the first stirring speed is 400-600rpm, the second stirring time is 20-30min, the second stirring speed is 400-600rpm, and the basement membrane is left to stand for 2h; In step S23, the three-stage calcination includes a first stage calcination, a second stage calcination, and a third stage calcination. The first stage calcination time is 50-70min, and the calcination temperature is 90-150°C. The second stage calcination time is 1.5-2.5h, and the calcination temperature is 280-320°C. The third stage calcination time is 3-5h, and the calcination temperature is 440-560°C. The three-stage calcination heating rate is controlled at 1-5°C / min.

[0012] The step S3 specifically includes: Step S31, after mixing the polyelectrolyte and the solvent, adding an acidic buffer to adjust the pH value to obtain an acidic ISE-PEL polyelectrolyte solution; Step S32, placing the nanosieve layer on the surface of the basement membrane in an acidic ISE-PEL polyelectrolyte solution for 10-30 minutes; Step S33, applying an asymmetric pulse electric field to the nano-sieve layer on the surface of the basement membrane during the static state for 10-30 minutes.

[0013] In the step S31, the mass percentage of the polyelectrolyte in the acidic ISE-PEL polyelectrolyte solution is 0.5-2%, the remainder is the acidic ISE-PEL polyelectrolyte solution, the mixing time of the polyelectrolyte and the solvent is 10-30 min, the mixing speed is 100-800 rpm, and the pH value of the acidic ISE-PEL polyelectrolyte solution is 4-5.

[0014] The step S4 specifically includes: Step S41, dissolving ammonium cerium nitrate and 2-methylimidazole in a solvent at a volume ratio of 1:1, mixing and stirring to obtain a mixed solution; Step S42, allowing the deposited film on the substrate film to stand in the mixed solution for 30-60 minutes, and performing ultrasonic treatment during the standing process; Step S43, introducing carbon dioxide into the mixed solution to promote the reaction between ammonium cerium nitrate and 2-methylimidazole to form a selective capture layer on the deposited film.

[0015] In step S43, the carbon dioxide ventilation flow rate is 50-100 mL / min, and the ventilation time is 30-60 min.

[0016] In step S5, after the amphiphilic triphenylene derivative solution is prepared, the amphiphilic triphenylene derivative solution is coated on the entire base film by a spin coater, and after ultraviolet light curing for 10-20 minutes, a dynamic hydrophobic layer is formed on the entire base film; In step S5, the spin coating of the spin coater is a two-stage spin coating, the first stage of the spin coating speed is 500-1000rpm, the time is 8-12s, and the second stage of the spin coating speed is 2000-3000rpm, the time is 30-60s.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention discloses a highly selective separation membrane and a preparation method thereof. Through the basement membrane, nano-sieve layer, deposition membrane and selective capture layer, the separation membrane can separate nitrate and nitrite with high selectivity when treating desulfurization wastewater, so as to reduce the interference of other inorganic salts and significantly improve the separation efficiency of the separation membrane. The porous structure of the basement membrane can effectively separate larger molecules and particulate matter, thereby achieving preliminary screening. After the desulfurization wastewater passes through the basement membrane, the and It passes through a nano-sieve layer, which has very small pores and can screen the ions more finely. and It can still pass through, while other macromolecules or particles are blocked. At the same time, the nano-sieve layer can further improve the blocking effect of other macromolecules or particles under the action of the deposited membrane. Finally, the desulfurized wastewater passes through the selective capture layer, which has a pore size of 0.35-0.45nm and has a positive charge, which can selectively adsorb through electrostatic action. and When the osmotic pressure acts on the desulfurization wastewater, the cerium ions and The weaker coordination bond is formed, and the flowing desulfurization wastewater, under the action of osmotic pressure, pushes the temporarily retained in the selective capture layer 4 and ,make and The desulfurized wastewater is discharged from the selective capture layer 4 along with the flowing desulfurized wastewater, and is carried away by the flowing desulfurized wastewater, thereby achieving and separation.

[0018] 2. The present invention provides a highly selective separation membrane and a preparation method thereof. By using sulfonated polyaryletherketone as a base membrane material, the separation membrane is endowed with excellent acid and alkali resistance and mechanical strength, ensuring that the separation membrane can work stably for a long time in a harsh chemical environment, reducing the maintenance and replacement frequency, and extending the service life of the equipment, thereby improving the economy and reliability. 3. The present invention provides a highly selective separation membrane and a method for preparing the same. By depositing a gradient charge structure of the membrane, divalent ions are strongly repelled from the membrane surface, while monovalent ions such as nitrate and nitrite can pass through effectively, further optimizing the permeability of nitrate and nitrite. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0020] The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportion or adjustment of size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical contents disclosed by the present invention.

[0021] Figure 1 It is a cross-sectional structural diagram of the high-selectivity separation membrane of the present invention; Figure 2 It is a flowchart of the method for preparing the high-selectivity separation membrane in the present invention.

[0022] Illustration: 1. Basement membrane; 2. Nano-sieve layer; 3. Deposition membrane; 4. Selective capture layer; 5. Dynamic hydrophobic layer. DETAILED DESCRIPTION

[0023] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] In the description of the present invention, it should be understood that the terms "upper", "lower", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present invention. It should be noted that when a component is considered to be "connected" to another component, it may be directly connected to the other component or there may be a centrally arranged component at the same time.

[0025] Embodiment 1: See also Figure 1 In this embodiment, a highly selective separation membrane is provided. The highly selective separation membrane comprises a dynamic hydrophobic layer 5 and a base membrane 1, a nano-sieve layer 2, a deposited membrane 3 and a selective capture layer 4 connected in sequence. The dynamic hydrophobic layer 5 is arranged on the outside of the base membrane 1, the nano-sieve layer 2, the deposited membrane 3 and the selective capture layer 4.

[0026] Specifically, the highly selective separation membrane comprises a base membrane 1, a nano-sieve layer 2, a deposition membrane 3, a selective capture layer 4 and a dynamic hydrophobic layer 5 wrapping the outside of the above four structures, and the highly selective separation membrane is effective in separating desulfurization wastewater. and (nitrate and nitrite), the desulfurization wastewater first passes through the dynamic hydrophobic layer 5 wrapped around the base membrane 1, the nanosieve layer 2, the deposition membrane 3, and the selective capture layer 4, and then passes through the base membrane 1, the nanosieve layer 2, the deposition membrane 3, the selective capture layer 4 in sequence, and is discharged from the dynamic hydrophobic layer 5.

[0027] The working principle of highly selective separation membranes is as follows: Applying high selectivity separation membrane to separate desulfurization wastewater and When the desulfurized wastewater first passes through the basement membrane 1, the porous structure of the basement membrane 1 can effectively separate larger molecules and particles, thereby achieving preliminary screening. After the desulfurized wastewater passes through the basement membrane 1, and It will pass through the nano-sieve layer 2, which has very small pores and can screen the ions more finely. and The nano-sieve layer 2 can still pass through, while other macromolecules or particles are blocked. At the same time, the nano-sieve layer 2 can further improve the blocking effect of other macromolecules or particles under the action of the deposition membrane 3. Finally, the desulfurized wastewater passes through the selective capture layer 4, which has a pore size of 0.35-0.45nm and has a positive charge, and can selectively adsorb through electrostatic action. and When the osmotic pressure acts on the desulfurization wastewater, the cerium ions and The weaker coordination bond is formed, and the flowing desulfurization wastewater, under the action of osmotic pressure, pushes the temporarily retained in the selective capture layer 4 and ,make and The desulfurized wastewater is discharged from the selective capture layer 4 along with the flowing desulfurized wastewater, and is carried away by the flowing desulfurized wastewater, thereby achieving and separation.

[0028] Embodiment 2: See also Figure 2 A method for preparing a highly selective separation membrane in this embodiment is used to prepare the highly selective separation membrane of embodiment 1. The preparation method comprises the following steps: Step S1, mixing sulfonated polyaryletherketone with sulfolane / tetrahydrofuran to obtain a mixed solution, and forming the mixed solution by microfluidic aerosol spraying, and drying and solidifying the mixed solution to obtain a basement membrane 1; Step S1 specifically includes: Step S11, after mixing the sulfonated polyaryletherketone and sulfolane / tetrahydrofuran, stirring at a constant temperature of 35-45° C. for 6-8 hours, and after the solution is stirred until it is completely transparent, a mixed solution is obtained; Step S12, injecting the mixed solution into a microfluidic aerosol spraying device, and under the impetus of high-purity nitrogen, spraying the mixed solution onto a low-temperature cold plate through a nozzle on the microfluidic aerosol spraying device to solidify and form, thereby obtaining a basement membrane 1 prototype; Step S13, placing the basement membrane 1 prototype in a drying device, and introducing carbon dioxide, and obtaining the basement membrane 1 after drying.

[0029] It should be noted that the base membrane 1 prepared by the mixed solution has high mechanical strength, porosity and hydrophilicity. The sulfonated polyaryletherketone in the mixed solution has sulfonic acid groups, which can give the base membrane 1 hydrophilicity and ion exchange capacity, thereby enhancing the and The selective adsorption of the mixed solution can be achieved, and the basement membrane 1 formed by injection molding of the microfluidic aerosol injection device has a porous structure with a porosity of 50-70% and a pore size range of 1-3um, which provides good permeability and support for the subsequent setting of the nano-sieve layer 2. At the same time, under the action of the low-temperature cold plate, the solidification rate of the mixed solution is controllable to ensure uniform pore distribution and pore penetration, and the low temperature environment of the cold plate avoids the problem of uneven pore size or collapse caused by rapid volatilization of the solvent.

[0030] It should also be noted that by introducing carbon dioxide to dry the basement membrane 1 prototype, the pore collapse of the porous structure caused by the surface tension of the solvent can be avoided, so that the structure of the porous structure is intact.

[0031] In addition, making sulfonated polyaryletherketone into the base membrane 1 can make the subsequently prepared high-selectivity separation membrane have excellent acid and alkali resistance, so that the separation membrane can be used in the environment of desulfurization wastewater.

[0032] Specifically, and The particle sizes are 0.34nm and 0.36nm respectively.

[0033] In step S11, the mass percentage of sulfonated polyaryletherketone in the mixed solution is 10-20%, the balance is sulfolane / tetrahydrofuran, and the viscosity of the mixed solution is 50-200 mPa·s; Preferably, the mass percentage of sulfonated polyaryletherketone in the mixed solution is 15%, the balance is sulfolane / tetrahydrofuran, the viscosity of the mixed solution is 100 mPa·s, the mixing time of sulfonated polyaryletherketone and sulfolane / tetrahydrofuran is 7 hours, and the mixing temperature is 40°C.

[0034] In step S12, the nozzle diameter is 10-50um, the injection pressure is 100-300kPa, the nozzle moving speed is 5-20mm / s, the nozzle injection flow rate is 1-10m / s, the distance between the nozzle and the cold plate is 1-3mm, the cold plate temperature is -30°C, and the molding time is 5-10min; Preferably, the nozzle diameter is 30 um, the injection pressure is 200 kPa, the nozzle movement speed is 10 mm / s, the nozzle injection flow rate is 50 m / s, the distance between the nozzle and the cold plate is 2 mm, and the molding time is 7.5 min.

[0035] In step S13, the drying temperature in the drying equipment is 35-45°C, the drying pressure is 10-12MPa, and the drying time is 1-2h.

[0036] Preferably, the drying temperature in the drying equipment is 40° C., the drying pressure is 44 MPa, and the drying time is 1.5 h.

[0037] It should be noted that when drying the prototype of the base membrane 1, the carbon dioxide is pressurized to reach a supercritical state. During the drying process, the residual solvent can be completely removed by the low surface tension characteristics of the carbon dioxide supercritical fluid. After the drying is completed, the pressure must be slowly reduced to discharge the carbon dioxide to avoid damage to the porous structure of the base membrane 1 after molding due to a sudden drop in pressure.

[0038] Step S2, providing a phosphate buffer, immersing the surface of the basement membrane 1 in the phosphate buffer, adding tetraethyl orthosilicate and ammonia water to the phosphate buffer, and after the reaction is completed, calcining the basement membrane 1 to form a nano-sieve layer 2 on the surface of the basement membrane 1; Step S2 specifically includes: Step S21, mixing disodium hydrogen phosphate dihydrate and potassium dihydrogen phosphate to obtain a phosphate buffer, and then placing the surface of the basement membrane 1 obtained in step S1 in the phosphate buffer and letting it stand for 10-30 minutes; Step S22, adding tetraethyl orthosilicate into the phosphate buffer solution and stirring once, then adding ammonia water dropwise and stirring for a second time, and allowing the surface of the basement membrane 1 to stand for 1-3 hours; Step S23 , after the base film 1 is taken out, cleaned and dried, the base film 1 is calcined through a three-stage calcination.

[0039] In step S21, the molar ratio of disodium hydrogen phosphate dihydrate to potassium dihydrogen phosphate is 1:1, the pH value of the phosphate buffer is 7.0, and the surface of the basement membrane 1 is left to stand for 20 minutes; It should be noted that after ethyl orthosilicate is dissolved in phosphate buffer, ethyl orthosilicate will be hydrolyzed to form silica molecules, which will then undergo a condensation reaction with ammonia water to form silica. When silica is deposited in the pores on the surface of the base membrane 1, a silica layer can be formed on the pores on the surface of the base membrane 1. In the subsequent calcination, the silica layer is densified under the action of calcination, organic residues are removed, and finally a nano-sieve layer 2 with sub-nanometer sieve channels with a pore size of 0.33±0.03nm is formed.

[0040] It should be noted that the nano-sieve layer 2 achieves preliminary screening of ions or molecules by limiting the pore size, and the sulfonic acid groups in the sulfonated polyaryletherketone can also assist the condensation reaction of silicate molecules with ammonia water.

[0041] In step S22, the mass percentage of tetraethyl orthosilicate in phosphate buffer is 1-5%, the mass percentage of ammonia water in phosphate buffer is 0.5-2%, the balance is phosphate buffer, the concentration of tetraethyl orthosilicate is 0.05-0.1M, the concentration of ammonia water is 25-28%, the first stirring time is 8-12min, the first stirring speed is 400-600rpm, the second stirring time is 20-30min, the second stirring speed is 400-600rpm, and the basement membrane 1 is left standing for 2h; Preferably, the mass percentage of ethyl orthosilicate in the phosphate buffer is 2%, the mass percentage of ammonia water in the phosphate buffer is 1%, the balance is phosphate buffer, the first stirring time is 10 min, the first stirring speed is 500 rpm, the second stirring time is 25 min, and the second stirring speed is 500 rpm; In step S23, the three-stage calcination includes first-stage calcination, second-stage calcination, and third-stage calcination. The first-stage calcination time is 50-70 min, and the calcination temperature is 90-150°C. The second-stage calcination time is 1.5-2.5 h, and the calcination temperature is 280-320°C. The third-stage calcination time is 3-5 h, and the calcination temperature is 440-560°C. The three-stage calcination heating rate is controlled at 1-5°C / min.

[0042] Preferably, the first stage calcination time is 60 minutes, the calcination temperature is 120°C, the second stage calcination time is 2 hours, the calcination temperature is 300°C, and the third stage calcination time is 4 hours, the calcination temperature is 500°C.

[0043] In a specific embodiment, after the nano-sieve layer 2 is prepared, its pore size can be detected by a transmission electron microscope to determine whether the prepared nano-sieve layer 2 is qualified. If the detected nano-sieve layer 2 meets 0.33±0.03nm, it is recorded as qualified. Otherwise, it is recorded as unqualified. If the nano-sieve layer 2 is qualified, subsequent preparation work is carried out. Otherwise, if the nano-sieve layer 2 is unqualified, it is discarded, and according to the corresponding relationship between the mass percentage of tetraethyl orthosilicate and ammonia water and the pore size of the nano-sieve layer 2, the mass percentage of tetraethyl orthosilicate and ammonia water in the phosphate buffer solution in the subsequent preparation process is adjusted so that the pore size of the nano-sieve layer 2 prepared subsequently meets the requirements; Specifically, an increase in the mass percentage of ethyl orthosilicate in the phosphate buffer will increase the number of silicic acid molecules generated by hydrolysis, thereby increasing the amount of silicon dioxide deposited on the surface of the basement membrane 1, thereby causing the pore size of the nano-sieve layer 2 to increase. Conversely, a decrease in the mass percentage of ethyl orthosilicate will reduce the generation of silicic acid molecules, and the pore size of the nano-sieve layer 2 will decrease. Increasing the mass percentage of ammonia water in the phosphate buffer will accelerate the polymerization process of silicic acid, forming a denser silicon dioxide layer, resulting in a reduction in the nano-sieve layer 2; decreasing the mass percentage of ammonia water will slow down the polymerization rate, thereby increasing the nano-sieve layer 2.

[0044] It can be known that this method can be used to indicate the preparation of separation membranes, so as to reduce defective products in the preparation process and thus reduce production costs.

[0045] For example, when the pore sizes of the nanosieve layer 2 are 0.29 nm, 0.31 nm, 0.33 nm, 0.35 nm, 0.37 nm, ..., respectively, the mass percentages of tetraethyl orthosilicate in the phosphate buffer are 1.6%, 1.8%, 2%, 2.2%, 2.4%, ..., respectively, and the mass percentages of ammonia water in the phosphate buffer are 1.2%, 1.1%, 1%, 0.9%, 0.8%, ..., respectively.

[0046] It is known that a transmission electron microscope is a commonly used tool for detecting pore size, which will not be described in this embodiment.

[0047] Step S3, providing an acidic ISE-PEL polyelectrolyte solution, immersing the nano-sieve layer 2 on the surface of the substrate membrane 1 therein, and subjecting the solution to an asymmetric pulse electric field treatment to form a deposited film 3 on the nano-sieve layer 2; Step S3 specifically includes: Step S31, after mixing the polyelectrolyte and the solvent, adding an acidic buffer to adjust the pH value to obtain an acidic ISE-PEL polyelectrolyte solution; Step S32, placing the nanosieve layer 2 on the surface of the substrate membrane 1 in an acidic ISE-PEL polyelectrolyte solution for 10-30 minutes; Step S33, applying an asymmetric pulse electric field to the nano-sieve layer 2 on the surface of the basement membrane 1 for 10-30 minutes.

[0048] It should be noted that, when the acidic ISE-PEL polyelectrolyte solution is connected to an asymmetric pulse electric field, polyelectrolyte molecules can be deposited on the nano-sieve layer 2 to form a deposited film 3 with a gradient charge distribution.

[0049] In addition, after the nano-sieve layer 2 on the substrate membrane 1 is subjected to the asymmetric pulse electric field treatment, the substrate membrane 1 needs to be cleaned and dried to remove the undeposited polyelectrolyte molecules on the nano-sieve layer 2 and form a deposited film 3 with a gradient charge structure. Under the action of the gradient charge structure, the deposited film 3 enhances the repulsion of divalent ions through electrostatic action and optimizes the monovalent ions, that is, and The penetration ability.

[0050] Specifically, the asymmetry of the electric field causes the polyelectrolyte molecules to form a higher charge density in the area close to the surface of the nanosieve layer 2 and a lower charge density in the area close to the inside of the nanosieve layer 2, so that the gradient charge structure of the deposited film 3 is a sparse structure on the outside and a dense structure on the inside. The gradient charge structure of the deposited film 3 can effectively repel divalent ions through the higher charge density on the surface and can effectively repel divalent ions through the lower charge density inside. and Can pass through effectively.

[0051] It should also be noted that the pore size of the nano-sieve layer 2 ensures that the polyelectrolyte molecules do not penetrate too deeply during deposition, avoiding the disorder of charge distribution, thereby ensuring the quality of the deposited film 3 with a gradient charge structure.

[0052] It should be noted that the nano-sieve layer 2 is electrostatically screened by the pore size and the deposition film 3. and Screening is carried out to form an efficient double separation, and the two complement each other.

[0053] In step S31, the mass percentage of the polyelectrolyte in the acidic ISE-PEL polyelectrolyte solution is 0.5-2%, the remainder is the acidic ISE-PEL polyelectrolyte solution, the mixing time of the polyelectrolyte and the solvent is 10-30 min, the mixing speed is 100-800 rpm, and the pH value of the acidic ISE-PEL polyelectrolyte solution is 4-5; Preferably, the mass percentage of the polyelectrolyte in the acidic ISE-PEL polyelectrolyte solution is 1%, the balance is the acidic ISE-PEL polyelectrolyte solution, the mixing time of the polyelectrolyte and the solvent is 20 min, and the mixing speed is 500 rpm.

[0054] In step S32, the standing time is 20 min, and in step S33, the standing time is 20 min.

[0055] It should also be added that the porous structure with a porosity of 50-70% on the base membrane 1 is the key to the formation of the nano-sieve layer 2. The porous structure with a porosity of 50-70% can ensure the uniform distribution of the sieve layer to ensure the separation of the nano-sieve layer 2. and At the same time, the gradient charge distribution of the deposited film 3 depends on the pore size limitation of the nanosieve layer 2, ensuring that the polyelectrolyte molecules will not penetrate too deeply during the deposition process. The pore size of the nanosieve layer 2 is also the key to affecting the formation of the gradient charge distribution of the deposited film 3. During the preparation process, if the pore size of the nanosieve layer 2 is too large or too small, it will lead to disordered charge distribution and unable to form a gradient charge distribution.

[0056] Step S4, providing a mixed solution of ammonium cerium nitrate and 2-methylimidazole, immersing the deposited film 3 on the nano-sieve layer 2 on the surface of the substrate film 1 in the mixed solution, and introducing carbon dioxide gas to form a selective capture layer 4 on the deposited film 3; It should be noted that after the ammonium cerium nitrate and 2-methylimidazole are mixed, the ammonium ions in the ammonium cerium nitrate will combine with the imidazole groups in the 2-methylimidazole to form a cerium-imidazole complex in the mixed solution. The cerium-imidazole complex will be deposited on the deposition film 3 to form a selective capture layer 4. The cerium-imidazole complex allows the selective capture layer 4 to have a three-dimensional network structure with a specific pore size and surface charge distribution. At the same time, the selective capture layer 4 can selectively capture the surface charge of ... and selectively adsorbs and excludes other anions, thereby further achieving and Screening to improve the desulfurization wastewater and separation effect.

[0057] Specifically, the pore size of the capture layer 4 is selected to be 0.35-0.45 nm, and the surface of the capture layer 4 is selected to have positive charges, which can be adsorbed by electrostatic action. and , and with the cooperation of the pore size of the nanosieve layer 2, other ions can be specifically separated.

[0058] Step S4 specifically includes: Step S41, dissolving ammonium cerium nitrate and 2-methylimidazole in a solvent at a volume ratio of 1:1, mixing and stirring to obtain a mixed solution; Step S42, placing the deposited film 3 on the base film 1 in the mixed solution for 30-60 minutes, and performing ultrasonic treatment during the standing process; Step S43, introducing carbon dioxide into the mixed solution to promote the reaction between ammonium cerium nitrate and 2-methylimidazole to form a selective capture layer 4 on the deposited film 3; In step S43, the carbon dioxide ventilation flow rate is 50-100 mL / min, and the ventilation time is 30-60 min.

[0059] Preferably, the carbon dioxide ventilation flow rate is 75 mL / min and the ventilation time is 45 min.

[0060] It should be noted that the passage of carbon dioxide in the mixed liquid can cause the carbon dioxide to react with the solvent in the mixed liquid to form carbonic acid, which can adjust the pH value of the mixed liquid to weak acidity. The weakly acidic mixed liquid can prevent the cerium-imidazole complex from forming too quickly and affecting the quality of the selective capture layer 4 after formation.

[0061] It should also be noted that the nano-sieve layer 2 can separate macromolecules and particles, achieve preliminary screening, and the deposited film 3 can then and Filter out, realize secondary screening, and then select capture layer 4 to selectively capture monovalent ions and , and separate the two, so as to achieve the desulfurization wastewater and Screening.

[0062] It is important to note that when selecting capture layer 4, and Afterwards, the cerium ions in the selective capture layer 4 will react with and The oxygen atoms in the ions are weakly coordinated to achieve weak adsorption, thus temporarily and Retained in the selective capture layer 4, and Under the osmotic pressure during desulfurization wastewater treatment, it will be discharged from the selective capture layer 4 along with the water flow, thereby achieving and separation.

[0063] It is known that in the process of treating desulfurization wastewater, osmotic pressure is needed to assist.

[0064] Specifically, when the osmotic pressure drives the desulfurization wastewater to flow, and With the weak adsorption of selective capture layer 4, and It can be discharged from the selective capture layer 4 along with the flow of the desulfurized wastewater to achieve separation, and in the process of the flow of the desulfurized wastewater, there is a continuous and Captured by the selected capture layer 4, after capture and It is then discharged from the selective capture layer 4 under the action of osmotic pressure, and the cycle repeats. and Can be continuously separated.

[0065] Step S5 , providing an amphiphilic triphenylene derivative solution, and spin coating it on the entire base film 1 , and after it is cured by ultraviolet light, a dynamic hydrophobic layer 5 is formed on the entire base film 1 .

[0066] In step S5, after the amphiphilic triphenylene derivative solution is prepared, the amphiphilic triphenylene derivative solution is coated on the entire base film 1 by a spin coater, and after ultraviolet light curing for 10-20 minutes, a dynamic hydrophobic layer 5 is formed on the entire base film 1. Preferably, the ultraviolet light curing is 15 minutes; It should be noted that the dynamic hydrophobic layer 5 composed of the amphiphilic triphenylene derivative solution makes the base membrane 1 have excellent hydrophobicity. Through the effect of hydrophobicity, the dynamic hydrophobic layer 5 can prevent grease, suspended matter and other macromolecular pollutants from adhering to the membrane surface, reduce the deposition of pollutants, and improve the membrane flux. At the same time, the dynamic hydrophobic layer 5 has good chemical resistance and wear resistance, and can withstand long-term water flow impact and chemical environment changes, thereby ensuring the long-term stability and performance of the base membrane 1.

[0067] In addition, the dynamic hydrophobic layer 5 can ensure the cleanliness of the separation membrane surface and the selective capture layer 4 surface, thereby and When passing through the base film 1, the nano-sieve layer 2, the deposition film 3 and the selective capture layer 4, it will not be disturbed by the outside world.

[0068] It should be added that the uniform deposition of the cerium-imidazole complex of the capture layer 4 depends on the gradient charge structure. The disordered distribution of the gradient charge of the deposited film 3 will lead to the uniform deposition of the cerium-imidazole complex, thereby affecting the and The adsorption capacity of the ions decreases.

[0069] In step S5, the spin coating is a two-stage spin coating, the first stage spin coating speed is 500-1000 rpm, the time is 8-12s, and the second stage spin coating speed is 2000-3000 rpm, the time is 30-60s.

[0070] Preferably, the first stage of spin coating has a rotation speed of 800 rpm and a duration of 10 s, and the second stage of spin coating has a rotation speed of 2500 rpm and a duration of 45 s.

[0071] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A highly selective separation membrane, characterized in that: The highly selective separation membrane comprises a dynamic hydrophobic layer (5) and a base membrane (1), a nano-sieve layer (2), a deposited membrane (3) and a selective capture layer (4) connected in sequence, wherein the dynamic hydrophobic layer (5) is arranged on the outside of the base membrane (1), the nano-sieve layer (2), the deposited membrane (3) and the selective capture layer (4).

2. A method for preparing a highly selective separation membrane, characterized in that: For preparing the highly selective separation membrane according to claim 1, the preparation method comprises the following steps: Step S1, mixing sulfonated polyaryletherketone with sulfolane / tetrahydrofuran to obtain a mixed solution, and forming the mixed solution by microfluidic aerosol spraying, and drying and solidifying the mixed solution to obtain a basement membrane (1); Step S2, providing a phosphate buffer solution, immersing the surface of the basement membrane (1) in the phosphate buffer solution, adding tetraethyl orthosilicate and ammonia water to the phosphate buffer solution, and after the reaction is completed, calcining the basement membrane (1) to form a nano-sieve layer (2) on the surface of the basement membrane (1); Step S3, providing an acidic ISE-PEL polyelectrolyte solution, immersing the nano-sieve layer (2) on the surface of the substrate membrane (1) therein, and subjecting the solution to an asymmetric pulse electric field treatment to form a deposited film (3) on the nano-sieve layer (2); Step S4, providing a mixed solution of ammonium cerium nitrate and 2-methylimidazole, immersing the deposited film (3) on the nano-sieve layer (2) on the surface of the substrate film (1) in the mixed solution, and introducing carbon dioxide gas to form a selective capture layer (4) on the deposited film (3); Step S5, providing an amphiphilic triphenylene derivative solution, and spin coating it on the entire base film (1), and after it is cured by ultraviolet light, a dynamic hydrophobic layer (5) is formed on the entire base film (1).

3. The method for preparing a highly selective separation membrane according to claim 2, characterized in that: The step S1 specifically includes: Step S11, after mixing the sulfonated polyaryletherketone and sulfolane / tetrahydrofuran, stirring at a constant temperature of 35-45° C. for 6-8 hours, and after the solution is stirred until it is completely transparent, a mixed solution is obtained; Step S12, injecting the mixed solution into a microfluidic aerosol spraying device, and under the impetus of high-purity nitrogen, spraying the mixed solution onto a low-temperature cold plate through a nozzle on the microfluidic aerosol spraying device to solidify and form, thereby obtaining a prototype of a basement membrane (1); Step S13, placing the prototype of the basement membrane (1) in a drying device, and introducing carbon dioxide, and after drying, obtaining the basement membrane (1).

4. The method for preparing a highly selective separation membrane according to claim 3, characterized in that: In the step S11, the mass percentage of the sulfonated polyaryletherketone in the mixed solution is 10-20%, and the viscosity of the mixed solution is 50-200 mPa·s; In step S12, the nozzle diameter is 10-50um, the injection pressure is 100-300kPa, the nozzle movement speed is 5-20mm / s, the nozzle injection flow rate is 1-10m / s, the distance between the nozzle and the cold plate is 1-3mm, the cold plate temperature is -30°C, and the molding time is 5-10min; In the step S13, the drying temperature in the drying equipment is 35-45°C, the drying pressure is 10-12MPa, and the drying time is 1-2h.

5. The method for preparing a highly selective separation membrane according to claim 2, characterized in that: The step S2 specifically includes: Step S21, mixing disodium hydrogen phosphate dihydrate and potassium dihydrogen phosphate to obtain a phosphate buffer, and then placing the surface of the basement membrane (1) obtained in step S1 in the phosphate buffer and letting it stand for 10-30 minutes; Step S22, adding tetraethyl orthosilicate into the phosphate buffer solution and stirring once, then adding ammonia water dropwise and stirring for a second time, and allowing the surface of the basement membrane (1) to stand for 1-3 hours; Step S23: After the base film (1) is taken out and cleaned and dried, the base film (1) is calcined by a three-stage calcination.

6. The method for preparing a highly selective separation membrane according to claim 5, characterized in that: In the step S21, the molar ratio of disodium hydrogen phosphate dihydrate to potassium dihydrogen phosphate is 1:1, the pH value of the phosphate buffer is 7.0, and the surface of the basement membrane (1) is left to stand for 20 minutes; In step S22, the mass percentage of tetraethyl orthosilicate in phosphate buffer is 1-5%, the mass percentage of ammonia water in phosphate buffer is 0.5-2%, and the balance is phosphate buffer. The concentration of tetraethyl orthosilicate is 0.05-0.1M, the concentration of ammonia water is 25-28%, the first stirring time is 8-12 minutes, the first stirring speed is 400-600 rpm, the second stirring time is 20-30 minutes, the second stirring speed is 400-600 rpm, and the basement membrane (1) is left to stand for 2 hours; In step S23, the three-stage calcination includes a first stage calcination, a second stage calcination, and a third stage calcination. The first stage calcination time is 50-70min, and the calcination temperature is 90-150°C. The second stage calcination time is 1.5-2.5h, and the calcination temperature is 280-320°C. The third stage calcination time is 3-5h, and the calcination temperature is 440-560°C. The three-stage calcination heating rate is controlled at 1-5°C / min.

7. The method for preparing a highly selective separation membrane according to claim 2, characterized in that: The step S3 specifically includes: Step S31, after mixing the polyelectrolyte and the solvent, adding an acidic buffer to adjust the pH value to obtain an acidic ISE-PEL polyelectrolyte solution; Step S32, placing the nanosieve layer (2) on the surface of the substrate membrane (1) in an acidic ISE-PEL polyelectrolyte solution for 10-30 minutes; Step S33, applying an asymmetric pulse electric field to the nano-sieve layer (2) on the surface of the basement membrane (1) during the static state for 10-30 minutes.

8. The method for preparing a highly selective separation membrane according to claim 7, characterized in that: In the step S31, the mass percentage of the polyelectrolyte in the acidic ISE-PEL polyelectrolyte solution is 0.5-2%, the remainder is the acidic ISE-PEL polyelectrolyte solution, the mixing time of the polyelectrolyte and the solvent is 10-30 min, the mixing speed is 100-800 rpm, and the pH value of the acidic ISE-PEL polyelectrolyte solution is 4-5.

9. The method for preparing a highly selective separation membrane according to claim 2, characterized in that: The step S4 specifically includes: Step S41, dissolving ammonium cerium nitrate and 2-methylimidazole in a solvent at a volume ratio of 1:1, mixing and stirring to obtain a mixed solution; Step S42, allowing the deposited film (3) on the base film (1) to stand in the mixed solution for 30-60 minutes, and performing ultrasonic treatment during the standing process; Step S43, introducing carbon dioxide into the mixed solution to promote the reaction between ammonium cerium nitrate and 2-methylimidazole to form a selective capture layer (4) on the deposited film (3); In step S43, the carbon dioxide ventilation flow rate is 50-100 mL / min, and the ventilation time is 30-60 min.

10. The method for preparing a highly selective separation membrane according to claim 2, characterized in that: In step S5, after the amphiphilic triphenylene derivative solution is prepared, the amphiphilic triphenylene derivative solution is coated on the entire base film (1) by a spin coater, and after ultraviolet light curing for 10-20 minutes, a dynamic hydrophobic layer (5) is formed on the entire base film (1); In step S5, the spin coating of the spin coater is a two-stage spin coating, the first stage of the spin coating speed is 500-1000rpm, the time is 8-12s, and the second stage of the spin coating speed is 2000-3000rpm, the time is 30-60s.

Citation Information

Patent Citations

  • Preparation method of titanium dioxide thin film for solar cell electrode

    CN101941803A

  • In-situ-mineralized super-hydrophilic cerium carbonate / polyelectrolyte nanofiltration membrane and preparation method thereof

    CN107670516A

  • Titanium dioxide nanotube array-cerium-doped lead dioxide coating filtering membrane as well as preparation method and application thereof

    CN116059838A

  • Composite membranes for separation of gas mixtures and a method of preparation thereof

    WO2013185739A1